Multiscale and Multiphysics Computational Frameworks for Nano- and Bio-Systems - Kim, Hyungjun; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
This volume develops multiscale and multiphysics simulation methods to understand nano- and bio-systems by overcoming the limitations of time- and length-scales. Here the key issue is to extend current computational simulation methods to be useful for providing microscopic understanding of complex experimental systems. This volume discusses the multiscale simulation approaches in nanoscale metal-insulator-metal junction, molecular memory, ionic transport in zeolite based fuel cell systems, dynamics of biomolecular ions, and model lung system. Based on the cases discussed here, the author suggests various systematic strategies to overcome the limitations in time- and length-scales of the traditional monoscale approaches.
1 Introduction -- 2 Negative Differential Resistance of Oligo (Phenylene Ethynylene) Self-Assembled -- Monolayer Systems: The Electric Field Induced Conformational Change Mechanism -- 3 Free Energy Barrier for Molecular Motions in Bistable [2]Rotaxane Molecular -- Electronic Devices -- 4 Sodium Diffusion through Aluminum-Doped Zeolite BEA System: Effect of Water -- Solvation -- 5 Experimental and Theoretical Investigation into the Correlation between Mass -- and Ion Mobility for Choline and Other Ammonium Cations in N2 -- 6 Structural Characterization of Unsaturated Phospholipids Using Traveling Wave.-Ion Mobility Spectrometry -- 7 Interfacial Reactions of Ozone with Lipids and Proteins in a Model Lung Surfactant.-System -- 8 Appendix.
Keywords: Chemistry; Nanochemistry; Biochemistry; Chemistry; Theoretical and Computational Chemistry; Nanochemistry; Biochemistry, general